TECHNOLOGY OF CAST INSTRUMENT INGOTS PRODUCTION OF HIGH-SPEED STEEL WITH INCREASED CONTENT OF CASRBON - F. I. Rudnitskij (Литьë и металлургия, 2009)
Investigation of influence of heightened carbon contents on structure and characteristics of high-speed steel P6M5 is carried out.